Sustainable Energy Planning and Management Vol 37 - Østergaard, Poul Alberg; Johannsen, Rasmus Magni (International Journal of Sustainable Energy Planning and Management, 2023)
This 37th volume of the International Journal of Sustainable Energy Planning and Management present novel analyses on the Nigerian electricity sector with focus on stakeholders in centralised and decentralised electricity supply. Analyses of Berlin-Brandenburg in Germany shows the prospects of 100 % renewable energy systems here. Industry is an important target in the energy transition, so a model is developed to analyse energy savings potentials. Within the heating sector, much of the individual dwellings in Central and Eastern Europe are impacted by a fuel trap, trapping them between two essentially undesirable options – biomass and natural gas. Also, within the residential sector, a new analysis probes in the feasibility of installing photo voltaics in India, and lastly, an interesting article investigates the local economic and employment effects of increased biofuel production.